1987
DOI: 10.1128/aac.31.9.1338
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ofloxacin after parenteral and oral administration

Abstract: In 10 volunteers, the pharmacokinetics of ofloxacin {HOE 280, DL 8280; (+)-9-fluoro-2,3-dihydro-3-methyl-10-(4-methyl-1-piperazinyl)-7-oxo-7H-pyrido-[1,2,3-deI [1,4] 1.4 liters/kg of body weight) suggested effective diffusion into the extravascular space. High total and renal clearances indicated primarily renal excretion with additional elimination pathways, such as tubular secretion and extrarenal elimination. After oral administration, absorption was excellent, and the absolute bioavailability following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
92
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 27 publications
10
92
2
Order By: Relevance
“…The presence of the methyl piperazine ring in ofloxacin probably leads to enhanced oral absorption and a long half-life (properties shown by other quinolones such as pefloxacin, fleroxacin, and difloxacin). Pharmacokinetic disposition and bioavailability have been previously studied in different study populations, and the bioavailability of ofloxacin has been reported to be 80 to 90% (1,2,4,5,7). There is a paucity of data, however, directly comparing oral (p.o.)…”
mentioning
confidence: 99%
“…The presence of the methyl piperazine ring in ofloxacin probably leads to enhanced oral absorption and a long half-life (properties shown by other quinolones such as pefloxacin, fleroxacin, and difloxacin). Pharmacokinetic disposition and bioavailability have been previously studied in different study populations, and the bioavailability of ofloxacin has been reported to be 80 to 90% (1,2,4,5,7). There is a paucity of data, however, directly comparing oral (p.o.)…”
mentioning
confidence: 99%
“…tested (6,11). In view of the satisfactory in vitro activities of these two quinolones, clinical trials to verify their efficacy in treating brucellosis are warranted.…”
mentioning
confidence: 99%
“…Tubular transport of enoxacin, norfloxacin, ciprofloxacin, and ofloxacin has also been inferred by high CLR/CLCR ratios or has been confirmed by demonstration of significant reductions in CLR when coadministered with probenecid, an inhibitor of anionic tubular transport (5,18,23,25,28,29). Even fleroxacin, which has a CLR/CLCR ratio below unity, appears to have probenecid-sensitive tubular secretion (22).…”
Section: Discussionmentioning
confidence: 99%